Further ethnic differences in the renal sodium-dopamine relationship: Its uncoupling in iranian but not in thai normotensive subjects - Julian A.J.H. Critchley (2018)
Dopamine is a natriuretic hormone and is synthesized in the kidney in response to a sodium load. This relationship results in a positive correlation between urinary sodium and dopamine outputs. Uncoupling of the renal sodium-dopamine relationship is reflected in a loss of this correlation and will result in the sluggish excretion of a sodium load. We measured 24-h urinary sodium and dopamine outputs in Thais and Iranians, who traditionally have very different dietary salt environments (salt-rich and salt-scarce, respectively). There was a highly significant positive correlation between sodium and dopamine in the Thais (r = 0.53, P < 0.001) but no suggestion of such a correlation in the Iranians (r = 0.03). We hypothesize that in some races the uncoupling of the renal sodium-dopamine relationship, possibly as a mechanism to help conserve dietary sodium, predisposes the race to the development of hypertension when the individuals encounter a salt-rich diet. © Gower Academic Journals Ltd.